The Importance of English Pronunciation in Our Life - Karunia Amanda Z; Salwa Salsabila; Shinta Nurfidha; Yani Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Accurate English pronunciation is essential for clear and efficient communication. It guarantees that concepts are grasped and helps avoid misunderstandings. Pronouncing words correctly boosts confidence when speaking and facilitates the easy and clear expression of ideas. By assisting people in accurately identifying and reproducing sounds, it also improves listening skills. Correct pronunciation makes a big impression and can open up more options in both professional and academic settings. In the end, mastering pronunciation improves relationships with people from different cultural backgrounds, promoting improved communication and international interaction.